Mobilization of Actors and Precipitating Factors in the Implementation of Affirmative Policies for the Economic Advancement of Indigenous Papuan Communities in Sorong City - Tajuddin, Tamrin; Sukri, ‎; Ibrahim, Muh. Akmal (KnE Social Sciences, 2025)
Collective action refers to the concept of relationships among members within a network who depend on each other’s resources. Field realities indicate that the economic conditions of the indigenous Papuan communities remain underdeveloped and require serious attention from the government. Based on this, the study aims to examine the role of trust and participation in the implementation of affirmative policies intended to promote economic improvement for indigenous Papuan communities in Sorong City. This study employs a qualitative approach, using data collection techniques such as observation, in-depth interviews, and documentation. The data used includes both primary and secondary sources, and it is analyzed using an interactive method. Informants in this study consist of key actors who are directly involved in the implementation of the affirmative policy. The findings of this study show that actor mobilization is carried out by the local government by involving traditional leaders, the Papuan People’s Assembly (MRP), and Papuan community groups in deliberative forums related to affirmative-based economic improvement policies. The identified precipitating factors include social pressure, economic disparities, and the push from special autonomy policies. The interactions among actors in the policy process further strengthen the formation of a policy network as a manifestation of collective action. However, the effectiveness of policy implementation in the field still faces obstacles such as capacity imbalances among actors and weak coordination among the involved parties.